DEVELOPMENT OF EDUCATIONAL TOURISM ATTRACTION SEKARMUKTI ECO-AGRO IN PANGSAN TOURIST VILLAGE, PETANG, BADUNG - Ni Ketut Suardani (Ride: Journal of Cultural Tourism and Religious Studies, 2023)
Badung Regency is one of the regions in Bali with abundant tourist attractions. It is also the area where the Local Original Revenue (PAD) is predominantly generated from the tourism sector. This is because Badung has a wide variety of attractions that are popular among tourists, making tourists willing to spend their money in the Badung Regency area. One of the tourist villages, Pangsan, offers attractive natural attractions such as rafting, cycling, and trekking, with the potential for development that can be packaged into attractive tourism packages. This research was conducted through observations and literature studies using various documents. The results of the research show that the knowledge about rural areas in formal learning processes is not as comprehensive as the real conditions in the field. Utilizing the tourism potential and providing education through activities such as planting ornamental plants, fruits, and vegetables is an effective means of educating and providing experiences for both domestic and international tourists.